Depressive disorders in long-term survivors of stroke. Associations with demographic and social factors, functional status, and brain lesion volume. - Sharpe, M; Hawton, K; Seagroatt, V; Bamford, J; House, A; Molyneux, A; Sandercock, P; Warlow, C (1994)
Sixty surviving patients from a community-based stroke register who had computerised tomography (CT) scan evidence of a single brain lesion were interviewed three to five years after their first ever stroke. Depression (DSM-III-R major depression, partially resolved major depression, and dysthymia) was present in 11 (18%) of the patients and was associated with impaired physical and cognitive functioning, greater age, residence in an institution, absence of a close personal relationship, and larger original brain lesion. Of these variables, only functional dependence (odds ratio 16.4; confidence interval 1.6-170), larger lesion volume (6.6; 1-50), and female sex (8; 1.1-56) remained significantly associated with depression after controlling for all other variables. We conclude that depression in long-term survivors of stroke has many of the same associations as depression in non-stroke elderly populations. Depression in long-term stroke survivors may also be associated with larger original brain lesions, although this requires confirmation in a prospective study.